2018
DOI: 10.3390/jcm7110407
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Irisin in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is characterized by progressive memory dysfunction, oxidative stress, and presence of senile plaques formed by amyloid beta (Aβ) accumulation in the brain. AD is one of the most important causes of morbidity and mortality worldwide. AD has a variety of risk factors, including environmental factors, metabolic dysfunction, and genetic background. Recent research has highlighted the relationship between AD and systemic metabolic changes such as glucose and lipid imbalance and insulin resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 133 publications
(188 reference statements)
1
49
0
5
Order By: Relevance
“…SCI process includes primary injury referring to mechanical compression to spinal cord, nerve roots and osseous structures at initial impact, and secondary injury resulting from subsequent neuroinflammation and oxidative stress. As is known, AMPK is a critical kinase participated in energy metabolism and a regulator of nuclear factor-kappaB (NF-κB), and neuroinflammation and oxidative stress are two vital pathogenesis involved in various diseases that are regulated by NF-κB (Csaki et al, 2009;Wang et al, 2019), it seems that irisin has some correlation with SCI. Here we tried to investigate the possible role of irisin in the remission of SCI in perspective of the secondary injury.…”
Section: Introductionmentioning
confidence: 99%
“…SCI process includes primary injury referring to mechanical compression to spinal cord, nerve roots and osseous structures at initial impact, and secondary injury resulting from subsequent neuroinflammation and oxidative stress. As is known, AMPK is a critical kinase participated in energy metabolism and a regulator of nuclear factor-kappaB (NF-κB), and neuroinflammation and oxidative stress are two vital pathogenesis involved in various diseases that are regulated by NF-κB (Csaki et al, 2009;Wang et al, 2019), it seems that irisin has some correlation with SCI. Here we tried to investigate the possible role of irisin in the remission of SCI in perspective of the secondary injury.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, irisin has regulatory effects on brain-derived neurotropic factor (BDNF) and glial cell-derived neurotropic factor (GDNF) [ 54 , 55 , 56 , 57 ]. BDNF is critical in the pathogenesis of chronic pain [ 58 ], whereas GDNF attenuates it [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is critical in the pathogenesis of chronic pain [ 58 ], whereas GDNF attenuates it [ 59 , 60 ]. Some studies have reported that irisin promotes BNDF expression, but this effect was limited to the brain and did not occur in the spinal cord or peripheral nervous system [ 54 , 55 , 56 ]. BDNF and GDNF are survival-promoting factors in motor neurons [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could represent a great advance in the understanding of neurodegenerative diseases, such as Alzheimer's disease, and could open the door for future therapeutic approaches in the management of these disorders, leading to an improvement of brain function. 8,[62][63][64][65] Irisin has already been studied as a molecular diagnostic marker for cardiovascular diseases. Decreased circulating irisin levels are associated with increased cardiovascular risk.…”
Section: Irisin and New Associationsmentioning
confidence: 99%